Strong geomagnetic disturbances and induced currents on Earth surface - Elias, Ana Georgina (2008)
Long-term variations in strong geomagnetic storms are analyzed and linked to electric fields induced on Earth. In fact, geomagnetic disturbances generate electric fields that drive currents in the Earth which may have significant effects on electrical systems and pipelines. The present study will be carried out using aa, AE and Dst index data to estimate long-term variations in strong geomagnetic disturbances. The results are extended then to the space weather topic through a rough assessment of the expected Earth electric field from measured horizontal components of the surface magnetic field, and also through a qualitative estimation of the consequent currents and voltages induced in a pipeline using the distributed source transmission line (DSTL) theory.